2002
DOI: 10.1002/ptr.987
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quercetin on plasma extravasation in rat CNS and dura mater by ACE and NEP inhibition

Abstract: The effects of quercetin on substance P-induced plasma protein extravasation (PE) in the rat dura mater, cerebellum, olfactory bulb and cortex and also its modulation by endopeptidases, angiotensin-converting enzyme (ACE) and neutral endopeptidase (NEP) were studied. PE was assessed by photometric measurement of extravasated Evans blue. Substance P (SP) and NEP or ACE inhibitors increased the PE in dura mater. Pretreatment with captopril or phosphoramidon potentiated PE induced by SP in the dura mater and cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…This suggests that quercetin metabolites could interfere with RAAS and inhibit ACE activity in vivo. Several studies reported that quercetin can reduce plasma extravasation by inhibiting ACE and endopeptidases (Cyrino, Cardoso, Hackl, &Willie, Riberio-do-Valle, Simoes, Gabilan, &Nicalou, 2001). These results could be due to the activity of active metabolites of quercetin such as quercetin-3-O-glucuronic acid.…”
Section: Ace Inhibitionmentioning
confidence: 99%
“…This suggests that quercetin metabolites could interfere with RAAS and inhibit ACE activity in vivo. Several studies reported that quercetin can reduce plasma extravasation by inhibiting ACE and endopeptidases (Cyrino, Cardoso, Hackl, &Willie, Riberio-do-Valle, Simoes, Gabilan, &Nicalou, 2001). These results could be due to the activity of active metabolites of quercetin such as quercetin-3-O-glucuronic acid.…”
Section: Ace Inhibitionmentioning
confidence: 99%
“…An elevated level of substance P has been documented to be a major risk factor for vascular dementia. Intravenous administration of substance P to rats has been shown to cause a significant increase in plasma extravasation, an effect abolished by pretreatment with an NK1 tachykinin antagonist (Cyrino et al 2002). It has also been reported that the activation of NK1 tachykinin receptors on vascular endothelium may contribute to cerebral edema (Stumm et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with an important role of SP in TBI, clinical and experimental studies have reported adverse effects of ACE [82] or NEP inhibition, the enzymes which degrade SP, as this exaggerates the effects of released SP [83]. Indeed, ACE and NEP inhibitors have been found to increase plasma extravasation [74]. …”
Section: Neurogenic Inflammationmentioning
confidence: 93%
“…Chemical, electrical or immunological stimulation, or treatment with capsaicin, was found to elicit a neurogenic inflammatory response in the dura mater but not the pia or cerebral cortex [73]. Similarly, intravenous administration of SP to rats has been shown to cause a significant increase in plasma extravasation in the dura mater, an effect abolished by pre-treatment with an NK1 tachykinin antagonist [74]. It was previously proposed that the activation of NK1 tachykinin receptors on vascular endothelium may contribute to cerebral oedema [75].…”
Section: Neurogenic Inflammationmentioning
confidence: 99%